Two-Lining of Highways Through Public Private Partnership Manual of Specifications and Standards - Planning Commission (Planning Commission, 2006)
The Government of India has initiated an ambitious National Highways Development Programme (NHDP) that relies substantially on Public Private Partnerships (PPPs) as a means of attracting private capital, improving efficiencies and reducing costs. Several states are pursuing similar programmes based on PPPs in state highways, while a few others are in different stages of the process.
Planning Commission Government of India
Planning Commission Government of India